Fluxos de capitais, fragilidade externa e regimes cambiais: uma revisão teórica - Gabriel,Luciano Ferreira (2008)
Capital Flows, External Fragility and Currency Regimes: A Theoretical Review. The major integration and deregulation of the international financial markets increased the degree of interdependence and risk of incompatibility between the financial and monetary policy adopted by different countries. The consequences of these facts are the financial instability and the currency crisis. In this article we develop arguments advocating that independent of the currency regime adopted the national policy makers should take into account, between other factors, the major capital mobility and the integrations of markets. One of the corollaries of our analyses is that countries should pursue policies that reduces the degree of short-term capital volatile by the adoption of capital controls or though measures of prudential supervision.